2018
DOI: 10.4067/s0718-95162018005001801
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogen fixing specie Sophora cassioides (Fabaceae), is nutritionally favored and their rhizosphere bacteria modified when is co-cultivated with the cluster root forming Embothrium coccineum (Proteaceae)

Abstract: The The hypothesis that Embothrium coccineum, a species able to solubilize P through cluster roots (CR) carboxylate exudation, makes P more available in volcanic depositions, thus facilitating the growth of other plant species such as the N-fixing Sophora cassioides was tested. In this work, seedlings of these two tree species were grown alone or co-cultivated for six months in greenhouse conditions with either pumice, a recent volcanic deposition with low P availability, or an organic commercial mix. Upon ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A substantial number of studies have revealed that the rhizosphere of plants harbors thousands of different rhizobacterial taxa that can establish beneficial (e.g., plant growth-promoting bacteria), detrimental (e.g., phytopathogens), or symbiotic (e.g., N 2fixing bacteria) interactions with their host plants (Hinsinger et al 2005;Zúñiga-Feest et al 2018). Currently, most studies in the rhizosphere involve the isolation of culturable rhizobacteria, where in terms of taxonomic affiliation, they are commonly limited to four phyla taxa (Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria), which are recognized as the most abundant bacterial groups in soils (Lauber et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of studies have revealed that the rhizosphere of plants harbors thousands of different rhizobacterial taxa that can establish beneficial (e.g., plant growth-promoting bacteria), detrimental (e.g., phytopathogens), or symbiotic (e.g., N 2fixing bacteria) interactions with their host plants (Hinsinger et al 2005;Zúñiga-Feest et al 2018). Currently, most studies in the rhizosphere involve the isolation of culturable rhizobacteria, where in terms of taxonomic affiliation, they are commonly limited to four phyla taxa (Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria), which are recognized as the most abundant bacterial groups in soils (Lauber et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…the reproductive output of Acaena decreased in the presence of Embothrium ). Similarly, in another study, the presence of Embothrium acted to increase the leaf protein content but reduce the relative growth rate of Sophora cassioides (Fabaceae) in a pumice substrate (Zúñiga‐Feest et al., ). Overall, our results provide empirical evidence of a negative feedback between a beneficiary species ( Embothrium ) and a benefactor species ( Acaena ) in line with findings from a global assessment where species in different environments were considered (Schöb, Callaway, et al., ).…”
Section: Discussionmentioning
confidence: 84%
“…Embothrium is a shade-intolerant species that colonizes highly disturbed areas where other tree species rarely occur, including areas with frequent volcanic ash deposition, lahars (layers of volcanic scoria subjected to high radiation and low night temperatures), glacial moraines, and along roadsides (Alberdi & Donoso, 2004;Veblen & Ashton, 1978). Previous studies have reported an increase in the formation of cluster roots in Embothrium in response to low levels of soil P and N availability (Piper et al, 2013;Zúñiga-Feest, Delgado, & Alberdi, 2010;Zúñiga-Feest et al, 2018).…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since tobacco is a dense nutrients feeder crop, more uptakes of P, K and S result in decreasing levels of these nutrients in the soil ( Table 1 ). On the other hand, bacteria species under Proteobacteria have also been reported to fix N in the soils and hence increasing soil total N after tobacco ( Table 1 ; Balsanelli et al., 2015 ; Trovero et al., 2018 ; Zúñiga-Feest et al., 2018 ). Chloroflexi, another dominant phylum identified in tobacco growing areas, reported to catalase Mn and also involved in the nitrification process in soils ( Sorokin et al., 2012 ; Baginski and Sommerhalter, 2017 ).…”
Section: Discussionmentioning
confidence: 99%